Las placillas del desierto. Construcción de espacio urbano en el despoblado de Atacama. Bolivia y Chile, 1870-1900 - Milton Godoy Orellana (Les Cahiers ALHIM)
The article analyzes the peopling of the Atacama Desert from the analysis of three placillas, a type of emerging urban settlement that occurred in Chile since the mid eighteenth century to the same period of the nineteenth century, characterized by the proximity of their locations to mining. These villages appeared distant from the political and military power of the plazas or central villages and their merchants and miners benefited from an adjacent farm were located. The article examines the construction of urban space in Placillas Cachinal de La Sierra, Esmeralda and Caracoles concerning their urban designs and the presence of the state apparatus. In this analysis, one may notice differences regarding the presence of the classic grid street plan, their greater or lesser level of planning, and the presence of state order manifested in the type of urban design that means using a grid street plan. Finally, I analyze the placillas in a time perspective changes noting that the concept has faced.